Detecção de adulteração de café torrado e moído com cascas de café e milho por espectroscopia no infravermelho - Nádia Reis (2012)
Coffee has been the target of fraudulent admixtures with several materials, including coffee husks and cheaper roasted grains such as corn. Given the successful application of spectroscopic methods in the field of food adulteration as fast and reliable routine techniques, the objective of this work was to evaluate the feasibility of employing DRIFTS (Diffuse Reflectance Fourier Transform Infrared Spectroscopy) for discrimination between roasted coffee and common adulterants such as roasted corn and coffee husks. Arabica coffee beans, coffee husks and ground corn kernels were submitted to light, medium and dark roasts at temperatures ranging from 200 to 260°C. Principal Components Analysis of the DRIFTS spectra (normalized or not) and of the first derivatives of the spectra provided separation of the samples into three groups: coffee, coffee husks and corn. Classification models were developed based on Linear Discriminant Analysis and recognition and prediction abilities of these models were 100%. Such results indicate that DRIFTS presents potential for the development of a fast and reliable analytical methodology for discrimination between coffee and its common adulterants.